Impact of different microwave treatments on food texture. Issue 6 (10th October 2021) - Kutlu, Naciye; Pandiselvam, Ravi; Saka, Irem; Kamiloglu, Aybike; Sahni, Prashant; Kothakota, Anjineyulu
Abstract: Electromagnetic waves are frequently used for food processing with commercial or domestic type microwave ovens at present. Microwaves cause molecular movement by the migration of ionic particles or rotation of dipolar particles. Considering the potential applications of microwave technique in food industry, it is seen that microwaves have many advantages such as saving time, better final product quality (more taste, color, and nutritional value), and rapid heat generation. Although microwave treatment used for food processing with developing technologies have a positive effect in terms of time, energy, or nutrient value, it is also very important to what extent they affect the textural properties of the food that they apply to. For this purpose, in this study, it has been investigated that the effects of commonly used microwave treatments such as drying, heating, baking, cooking, thawing, toasting, blanching, frying, and sterilization on the textural properties of food. In addition, this study has also covered the challenges of microwave treatments and future work. In conclusion, microwave treatments cause energy saving due to a short processing time. Therefore, it can be said that it affects the textural properties positively. However, it is important that the microwave processing conditions used are chosen appropriately for each food material.